THE ROLE OF SPIRITUAL AND EDUCATIONAL ACTIVITIES IN THE FORMATION OF SOCIAL CONSCIOUSNESS AT THE STUDENT AGE - Orzikulov Khusniddin Tolkin ogli (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the role of spiritual and educational activities in the formation of public consciousness of students and the expansion of the worldview of youth.